Cost-benefit analysis concepts and practice - Boardman, Anthony E.; Greenberg, David H.; Vining, Aidan R.; Weimer, David Leo (Cambridge University Press, 2018)
A practical introduction to cost-benefit analysis through problem solving. This authoritative, market-leading text is known for its consistent application of a nine-step framework for conducting or interpreting a cost-benefit analysis.